Beyond Tradition: Transforming Micro and Medium Finance through Islamic Financial Innovations - Sefrita Yandri, Melani; Alfian, Alfian (Takaza Innovatix Labs Ltd., 2025)
This research explores the impact of Islamic financial innovations on enhancing access to micro and medium finance in developing countries. Focusing on models such as Murabaha, Mudarabah, and Ijarah, the study demonstrates how these Sharia-compliant financial products have significantly improved financial inclusion for underserved populations and small businesses. Despite notable successes, challenges such as regulatory inconsistencies, a lack of standardized guidelines, and limited professional expertise continue to impede the full potential of these innovations. Nevertheless, opportunities for growth exist through the leveraging of digital platforms and strengthening collaborations between financial institutions and regulators. The findings emphasize the necessity for supportive regulatory frameworks and ongoing adaptation to local contexts to enhance the effectiveness and sustainability of Islamic finance innovations in promoting economic development. Recommendations for practice include investing in staff training and adopting advanced digital tools, while policymakers are urged to develop clearer regulations that cater to the unique characteristics of Islamic finance. Additionally, future research should examine the long-term impact of these innovations and explore the integration of emerging technologies into Sharia-compliant finance. Overall, this research contributes to understanding how Islamic finance can drive inclusive and sustainable economic growth in developing regions.